The dynamics of the winner–loser gap in satisfaction with democracy: Evidence from a Swedish citizen panel. Issue 5 (November 2017) - Dahlberg, Stefan; Linde, Jonas
Several studies have demonstrated a gap in support for the political system between electoral winners and losers. This research has generated a large stock of knowledge about the causes and effects of this winner–loser gap. However, we know little about the dynamics of the winner–loser gap over time. Drawing on a unique Swedish panel survey, this study investigates the stability of the winner–loser gap among Swedish voters over an electoral cycle of four years. The empirical analyses demonstrate a substantial consistency of the gap over time also when controlling for other determinants. The winner–loser gap thus seems to be a stable phenomenon rather than a short-lived election effect. The results are robust to different specifications and statistical techniques.